THE ROLE OF MUSICAL CONSTRUCTION IN APPROACHING AND RENDERING OF OP. 52 LIEBESLIEDER-WALZER BY JOHANNES BRAHMS - PARA, Ciprian (Studia Universitatis Babes-Bolyai Musica, 2025)
In this article, I have outlined several aspects related to the musical structure and the conducting approach to the Brahms work for its interpretation. We adapted our interpretive concept to what the waltz means, and in the 18 pieces written in ternary meter, I presented some rhythmical-melodic formulas specific to the waltz. A specific aspect of Brahms’s music was the use of hemiolas, both in the vocal/choral part and in the piano accompaniment, which do not disrupt the flow of the musical discourse. In this regard, I proposed my own scheme for the articulation of each piece among the 18 waltzes, constituting an important element of my interpretative vision.